2017
DOI: 10.1186/s12906-017-1595-5
|View full text |Cite
|
Sign up to set email alerts
|

Medication use by middle-aged and older participants of an exercise study: results from the Brain in Motion study

Abstract: BackgroundOver the past 50 years, there has been an increase in the utilization of prescribed, over-the-counter (OTC) medications, and natural health products. Although it is known that medication use is common among older persons, accurate data on the patterns of use, including the quantity and type of medications consumed in a generally healthy older population from a Canadian perspective are lacking. In this study, we study the pattern of medication use in a sedentary but otherwise healthy older persons use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“… 37 A study of 3,072 outpatients aged 75 and older in the USA found that 82.5% of the studied cohort took at least one nutritional supplement, and 54.5% 3 or more. 38 In a study by Pannu et al, 39 81.5% of the respondents took at least one natural health product and 64.2% at least one OTC drug. In the USA, almost half of the elderly population regularly takes at least one OTC drug or supplement.…”
Section: Discussionmentioning
confidence: 98%
“… 37 A study of 3,072 outpatients aged 75 and older in the USA found that 82.5% of the studied cohort took at least one nutritional supplement, and 54.5% 3 or more. 38 In a study by Pannu et al, 39 81.5% of the respondents took at least one natural health product and 64.2% at least one OTC drug. In the USA, almost half of the elderly population regularly takes at least one OTC drug or supplement.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, work pressure or other stress-induced high blood pressure was related to mental health problems and disease-specific quality of life. Other chronic diseases also have been linked to diet; in terms of dietary modification, increased fruit and vegetable intake can decrease the risk of hypertension, obesity, and type 2 diabetes [ 9 , 33 ]. Similar to previous reports, our data indicated that middle-aged adults significantly preferred to choose vegetarian diets (79.1%), use CAMs (72.9%), and had less chronic disease (1.2 ± 1.4) than the older adult population during the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%